Peran Kepala Desa dalam Meningkatkan Partisipasi Masyarakat Pada Pembangunan di Desa Warukin Kecamatan Tanta Kabupaten Tabalong - Miranti Miranti; Lukman Arif (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Participation is the involvement or participation of a person in certain activities or often related to development activities. The purpose of this study was to describe and analyze the role of the village head in increasing community participation in development in Warukin Village, Tanta District, Tabalong Regency. The type of research used in this research was descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The research location was in Warukin Village, Tanta District, Tabalong Regency. The focus of the research was the role of the village head in increasing community participation in development in Warukin Village, Tanta District, Tabalong Regency. Sources of research data were primary data and secondary data. In summary, the results of the study stated that the village head had provided opportunities for the community to participate in the Village Musrembang. It increased the willingness of the community to participate in activities organized by the village government and the community's ability to participate in village development activities.